Kewarganegaraan dan Pertanggungjawaban Pidana: Studi Kasus Pengadilan Internasional - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Sinta Amalia; Jamilatul Dwi Aulia Khasanah; Fina Nailissa’adah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines issues related to citizenship and criminal responsibility in the context of international courts, with a focus on how these challenges influence law enforcement processes. Through a case study-based qualitative analysis approach and a review of recent literature, this research explores how dual citizenship, the political status of perpetrators, and globalization influence jurisdiction and justice in international courts. Case studies analyzed include The Prosecutor v. Al-Bashir and The Prosecutor v. Dominic Ongwen, who shows how these issues hamper international courts' efforts to enforce the law. The findings of this research underscore the need for reform in the international legal system, including legal harmonization, reform of extradition mechanisms, and increased coordination between courts. This research also highlights the importance of continuous education and training for international law officials to face new challenges in the era of globalization.